Analisis Strategi Eksistensi Toko Kelontong Dalam Menghadapi Perkembangan Pasar Modern Di Kabupaten Tebo - Windi Herlin Dera; Faturahman Faturahman; Atar Satria Fikri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The role of modern markets, especially Alfamart and Indomaret in Indonesia, is getting bigger and is expected to eventually replace grocery stores. The existence of modern markets also raises different perceptions from every circle of society. There are some groups of people who view the existence of modern markets positively. For example, for the upper middle class, the existence of modern markets is very beneficial because they can shop comfortably and freely in modern markets. The existence of this modern market can also affect the income of traditional market traders. One of the most important factors for Grocery Store entrepreneurs is the revenue generated from their profits to maintain business continuity. The purpose of this study is to determine the strategy for the existence of grocery stores in dealing with the development of modern markets in Tebo district. In this study the method used was qualitative method by checking the validity of the data using the triangulation technique and the method of collecting data was using observation and interviews. The informants in this study were five traders and five consumers. Based on the results of this study, it shows that the existence of Alfamart/Indomaret in Tebo Tengah District, Tebo Regency has an impact on income and the number of consumers of grocery store traders, but grocery store traders try to survive by adding side businesses so that their business continuity is maintained